A Comparison of Sepsis-2 (Systemic Inflammatory Response Syndrome Based) to Sepsis-3 (Sequential Organ Failure Assessment Based) Definitions—A Multicenter Retrospective Study*. Issue 9 (September 2020) - Engoren, Milo; Seelhammer, Troy; Freundlich, Robert E.; Maile, Michael D.; Sigakis, Matthew J. G.; Schwann, Thomas A.
Abstract : Objectives: Recently, the definition of sepsis has changed from a physiologic derangement (Sepsis-1 and -2) to organ dysfunction (Sepsis-3) based. We sought to determine the concordance between the different sepsis phenotypes and how that affected mortality. Design: Retrospective, multicenter study. Setting: Three academic medical centers. Patients: 29, 459 patients who had suspected infection, defined as obtaining blood cultures and receiving antibiotics: 18, 183 (62%) had either Sepsis-2 or Sepsis-3. Measurements and Main Results: Kappa was used to show agreement between phenotypes. Conditional logistic regression was used to create models of associations between factors and phenotypes and between factors and mortality. About 12, 981 patients had Sepsis-2; 12, 043 had Sepsis-3; and 6, 841 patients had both Sepsis-2 and Sepsis-3. Fifty-three percent of Sepsis-2 patients also had Sepsis-3, whereas 57% of Sepsis-3 patients also had Sepsis-2. Agreement between the two phenotypes was poor: kappa = 0.213 ± 0.006. Mortality was 6% in patients with only Sepsis-2, 10% with only Sepsis-3, and 18% in patients who had both phenotypes. Combining the variables in Sepsis-2 and Sepsis-3 improved the discrimination (C-statistic = 0.742 ± 0.005, p < 0.001) of mortality. Conclusions: We found that Sepsis-2 and Sepsis-3-based sepsis diagnoses represent separate phenotypes with poor agreement. Patients who have both phenotypes are at increased risk of mortality compared with having either phenotype alone. Inclusion of both systemic inflammatory response syndrome and Sequential Organ Failure Assessment criteria in the same model improves the discrimination of mortality. Abstract : Supplemental Digital Content is available in the text.